Inductive logic programming applied for knowledge representation in computer music - Gonçalves Junior, Clenio Batista; Homem, Murillo Rodrigo Petrucelli (Universidade Federal de São Carlos, 2021)
In Computer Music, the knowledge representation process is an essential element for the development of systems. Methods have been applied to provide the computer with the ability to generate conclusions based on previously established experience and definitions. In this sense, Inductive Logic Programming presents itself as a research field that incorporates concepts of Logic Programming and Machine Learning, its declarative character allows musical knowledge to be presented to non-specialist users in a naturally understandable way. The present work performs a systematic review based on approaches that use Inductive Logic Programming in the representation of musical knowledge. Questions that these studies seek to address were raised, as well as identifying characteristic aspects related to their application.
Programação lógica indutiva aplicada para representação do conhecimento em música computacional
Keywords: Computer music; Inductive logic programming; Knowledge representation; Artificial intelligence; Machine learning; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO